Neuroactive Steroids and GABAergic Involvement in the Neuroendocrine Dysfunction Associated With Major Depressive Disorder and Postpartum Depression - Maguire, Jamie (Frontiers in Cellular Neuroscience, 2019)
Stress and previous adverse life events are well-established risk factors for depression. Further, neuroendocrine disruptions are associated with both major depressive disorder (MDD) and postpartum depression (PPD). However, the mechanisms whereby stress contributes to the underlying neurobiology of depression remains poorly understood. The hypothalamic-pituitary-adrenal (HPA) axis, which mediates the body’s neuroendocrine response to stress, is tightly controlled by GABAergic signaling and there is accumulating evidence that GABAergic dysfunction contributes to the impact of stress on depression. GABAergic signaling plays a critical role in the neurobiological effects of stress, not only by tightly controlling the activity of the HPA axis, but also mediating stress effects in stress-related brain regions. Deficits in neuroactive steroids and neurosteroids, some of which are positive allosteric modulators of GABAA receptors (GABAARs), such as allopregnanolone and THDOC, have also been implicated in MDD and PPD, further supporting a role for GABAergic signaling in depression. Alterations in neurosteroid levels and GABAergic signaling are implicated as potential contributing factors to neuroendocrine dysfunction and vulnerability to MDD and PPD. Further, potential novel treatment strategies targeting these proposed underlying neurobiological mechanisms are discussed. The evidence summarized in the current review supports the notion that MDD and PPD are stress-related psychiatric disorders involving neurosteroids and GABAergic dysfunction.